Amiodarone‐ and Lithium‐Induced Thyroid Dysfunction—Prescriber Specialties Involved in Potential Prescribing Cascades: A Retrospective Study - J. de Ruijter – van Dalem; M. de Weerd – Slot; M. H. Schipper; C. E. H. Siegert; A. Marmorale; M. L. Becker; F. Karapinar‐Çarkit (Health Science Reports, 2026)
ABSTRACT Background and Aims Prescribing cascades occur when an adverse drug reaction (ADR) leads to the prescription of additional medications. It remains unclear whether different prescribers are involved in potential prescribing cascades that develop over time and whether ADRs are communicated across the care continuum. This study aimed to investigate whether the specialty of the prescriber initiating amiodarone or lithium differs from the specialty of the prescriber starting the thyroid medication and the communication of this ADR. Methods A retrospective study, combined with a structured questionnaire among community pharmacists, was conducted in two teaching hospitals and 22 community pharmacies from February 2023 to June 2023, including patients who initiated amiodarone or lithium and subsequently received thyroid medication within 24 months, regardless of whether this was intentional or unintentional. Primary outcome was whether prescribers' specialties differed. Secondary outcomes included the documentation of the ADR when thyroid medication was started and ADR communication in discharge letters. Community pharmacists were questioned to assess their awareness of this ADR. Descriptive statistics were used for data analysis. Results We included 67 hospital patients and 57 community pharmacy patients. Different specialties were involved in 49% of hospital patients and 81% of patients in the community setting with a potential amiodarone‐ or lithium‐induced thyroid dysfunction. In the hospital, the risk of thyroid dysfunction or the occurrence of the amiodarone‐induced prescribing cascade was documented in 78% of the patient records and/or discharge letters. Three percent of discharge letters noted thyroid dysfunction risks at amiodarone initiation. Questionnaires completed by community pharmacists revealed limited self‐reported awareness of this ADR and potential cascade. Conclusion Potential prescribing cascades with amiodarone and lithium‐induced thyroid dysfunction frequently involve different specialties. However, in this study, risks of ADRs were rarely communicated to subsequent healthcare providers. This discontinuity in information transfer represents opportunities for optimization of care.